The Influence of mobile money on savings behavior - OCHIENG, Kevin Oluoch (KDI School, 2023)
Mobile Money is a technology that facilitates financial service transactions via mobile phone without necessarily having internet connection. Registered users can send, receive, withdraw, deposit, and save money electronically in their phone which then eases financial access. In the African continent, Kenya is the pioneer of mobile money invention since 2007 when Kenyan telco giant Safaricom PLC launched the flagship Mobile Money service called “MPESA”. This research, therefore, explores how mobile money influences savings behavior paying attention to the financially disadvantaged group in Kenya, the youth. Using a four-wave FinAccess household survey data collected between 2006 and 2016 to estimate the demand and access of monetary services among adults in Kenya, the study runs a logistic regression model to measure the likelihood that a mobile money user has a savings product and analyzes commonly used savings platforms among mobile money users. As a robustness check and to deal with endogeneity concerns, the study employs the use of 2SLS IV model instrumenting proximity to mobile money agents against mobile money use. Results show that, there is 0.56 times likelihood that users of Mobile Money have a savings product compared to non-users. Secondly, Mobile Money users are also more inclined to savings in informal savings platforms such as ROSCAs and ASCAs compared to formal platforms such as banks, MFIs, and Saccos. As a policy issue therefore, formal financial institutions need to redesign their financial products to shift the youth’s preference from savings in informal platforms to formal platforms. Mobile network operators also need to capitalize on the youth’s preference to Mobile Money system to expand service provision and access even in the rural settings.
Thesis(Master) -- KDI School: Master of Devemopment Policy, 2023
Keywords: Financial services industry--Kenya; Digital currency--Kenya; Banks and banking--Technological innovations--Kenya